Evaluation Of Achievement Development Program Handball Sport Branch Province Of Central Java - Kukuh Ari Novenda; Bambang Priyono; Fajar Awang Irawan (STKIP Muhammadiyah Kuningan, 2023)
The Sports Branch needs to evaluate the achievement coaching program to keep developing with maximum achievement. This study aims to find out the antecedents (input) regarding the planning of ABTI Central Java achievement development, Transaction (process) regarding the implementation of the ABTI Central Java achievement development program, Outcomes (results) regarding the effects of Central Java ABTI achievement development. The type of research used is descriptive, using a qualitative approach. The type of data used is primary and secondary. Data collection was carried out using interviews and documentation observation techniques. Respondents in this study included administrators, Central Java ABTI managers, Central Java handball coaches, and athletes. The data analysis method used is the countenance evaluation or stake model. The study results showed that the antecedents in the planning of Central Java ABTI achievement development had gone well by the background, vision, mission, and the appropriate form of the coaching program. The transaction for implementing the ABTI Central Java achievement development program has been going well. Still, several elements need improvements, such as facilities and infrastructure, and financing. The outcomes evaluation of the achievement coaching program has been going well. Still, there is a need for management improvements to improve the achievements obtained in the championships that have been participated in before. Provincial administrators need to pay attention to the welfare of outstanding athletes. KONI Central Java provides a budget for the activities that have been proposed previously. ABTI Central Java management needs to activate all administrators by work jobs based on their respective divisions to expedite the process of coaching and training Central Java handball and get results per the planned goals.